2021
DOI: 10.1155/2021/6665938
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pyogenic Osteomyelitis of the Pubic Bone in a Patient with Systemic Lupus Erythematosus Mimicking Fracture of the Pubic Bone and Periprosthetic Joint Infection of the Hip

Abstract: Introduction. Pubic bone osteomyelitis is atypical, and the diagnosis is often overlooked. It may present as osteitis pubis, fracture, or noninfectious inflammation of the pubic symphysis. Case Report. We report a case of a 65-year-old lady who has systemic lupus erythematosus with acute pyogenic osteomyelitis of the pubic bone who presented initially with a suspicious healing pubic rami fracture and periprosthetic infection of the hip joint. Conclusion. Acute osteomyelitis of the pubic bone has often an infre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 15 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…Infections strongly affect morbidity and mortality in SLE [ 57 , 59 ]. Herrinton et al reported a six- to seven-fold greater risk of serious infection than the general population [ 60 ], mainly due to impaired function of immune system and immunosuppressive treatment [ 59 , 61 ]. Infections may be life-threatening and represent one of the leading causes of death in SLE [ 60 , 62 , 63 ], accounting for 25% to 50% of overall mortality [ 63 ].…”
Section: Sle and Osteomyelitismentioning
confidence: 99%
See 4 more Smart Citations
“…Infections strongly affect morbidity and mortality in SLE [ 57 , 59 ]. Herrinton et al reported a six- to seven-fold greater risk of serious infection than the general population [ 60 ], mainly due to impaired function of immune system and immunosuppressive treatment [ 59 , 61 ]. Infections may be life-threatening and represent one of the leading causes of death in SLE [ 60 , 62 , 63 ], accounting for 25% to 50% of overall mortality [ 63 ].…”
Section: Sle and Osteomyelitismentioning
confidence: 99%
“…OM is more frequent in SLE patients than in the general population [ 57 , 59 ], moreover occurring at a younger age [ 57 ]. Several studies and case reports described OM in SLE, due to different microorganisms [ 50 , 59 , 61 , 67 , 68 , 69 , 70 ] and affecting mainly bones of the lower limbs, in particular tibia and femur [ 57 , 59 ].…”
Section: Sle and Osteomyelitismentioning
confidence: 99%
See 3 more Smart Citations